2010
DOI: 10.1186/1471-2105-11-s1-s47
|View full text |Cite
|
Sign up to set email alerts
|

Computational prediction of type III secreted proteins from gram-negative bacteria

Abstract: BackgroundType III secretion system (T3SS) is a specialized protein delivery system in gram-negative bacteria that injects proteins (called effectors) directly into the eukaryotic host cytosol and facilitates bacterial infection. For many plant and animal pathogens, T3SS is indispensable for disease development. Recently, T3SS has also been found in rhizobia and plays a crucial role in the nodulation process. Although a great deal of efforts have been done to understand type III secretion, the precise mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 31 publications
(49 reference statements)
2
73
0
Order By: Relevance
“…As a consequence, computational methods used to detect secretion signals are only partially accurate (2,36,50,60,64). Our experiments with SrfJ fragments fused to CyaA showed that the minimal signal sequence necessary for translocation is contained in the N-terminal 20 amino acids of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, computational methods used to detect secretion signals are only partially accurate (2,36,50,60,64). Our experiments with SrfJ fragments fused to CyaA showed that the minimal signal sequence necessary for translocation is contained in the N-terminal 20 amino acids of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…1b). Yang et al (31) reported that the Bll8244 protein in B. diazoefficiens USDA 110 is a T3SS effector. Around the MA20_12780 gene, a transposase (MA20_12740), the IS1631 terminal repeat, and hypothetical genes were identified (Fig.…”
Section: Identification Of the Gene Disrupted By Tn5mentioning
confidence: 99%
“…We believe that a more likely scenario is that the physical and/or chemical characteristics of N-terminal residues in YopD FrameϪ1 fortuitously combine to enable its continued secretion. Of significance is the recent prediction that the overall amphipathicity of the N-terminal secretion signal, with an enrichment of serine, threonine, and proline and, possibly, even short stretches of hydrophobic residues, is a characteristic of a working T3S signal (6,48,64,84). Interestingly, YopD FrameϪ1 still harbors an N terminus interspersed with hydrophobic residues and a relatively high proportion (5 of 15) of serine, threonine, and/or proline residues, a pattern also observed for other secretion-competent YopD N-terminal sequences (see Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…A chaperoneindependent secretion signal also exists at the extreme N terminus, represented by a complex combination of the mRNA with the protein sequence (16,46,69). While no sequence consensus is visually obvious, there is some evidence of an amphipathic property (47), and various computational approaches based on sophisticated machine-learning methodology can predict T3S substrates on the basis of a conserved secretion signal (6,48,64,84). Nevertheless, the molecular contribution these extensively mapped chaperone-independent signals make to substrate secretion is not yet understood.…”
mentioning
confidence: 99%